2003
DOI: 10.1093/alcalc/agg049
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Activation by Murine Retroviral Infection During Chronic Ethanol Consumption

Abstract: These findings suggest that neutrophil function is impaired by LP-BM5 retrovirus infection and/or chronic ethanol consumption. The pattern of neutrophil CD11b expression and ROS production might help to predict the stage of murine AIDS. Ethanol may further compromise neutrophil function in AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The choice here of using doses of ethanol in quantities not toxic to liver was based on previous observations that mice exposed orally for a prolonged time to such a regimen did not suffer any visible damage to internal organs (30). This choice is indeed supported and extended by our study, which shows that at the dosage regimen used the mice did not suffer any metabolic consequences.…”
Section: Discussionsupporting
confidence: 58%
“…The choice here of using doses of ethanol in quantities not toxic to liver was based on previous observations that mice exposed orally for a prolonged time to such a regimen did not suffer any visible damage to internal organs (30). This choice is indeed supported and extended by our study, which shows that at the dosage regimen used the mice did not suffer any metabolic consequences.…”
Section: Discussionsupporting
confidence: 58%
“…Peripheral blood neutrophils from infected gal3 −/− were compared to those from gal3 +/+ mice for the levels of activation marker CD11b ( 35 ). Results in Figure 6 A showed that CD11b on neutrophils from gal3 −/− mice were significantly higher than cells from gal3 +/+ mice after infection (Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Less naïve Ag-specific T cell proliferation contributes to a poor adaptive immune response to pathogens and increased susceptibility to infection seen in alcoholism. In addition, marginal DC inflammatory cytokine production may also partially explain observed deficiencies in innate immunity following EtOH feeding as well (Boyadjieva et al, 2001; Chen et al, 2003; Frank et al, 2004; Laso et al, 1997; Laso et al, 2007b; Morio et al, 2000; Pan et al, 2006; Silvain et al, 1995). …”
Section: Discussionmentioning
confidence: 99%